Pengembangan Desa Wisata Edelweiss di Desa Wonokitri Kecamatan Tosari Kabupaten Pasuruan (Resort PTN Gunung Penanjakan Taman Nasional Bromo Tengger Semeru) - Pratiwi, Tityas Indra; Muttaqin, Tatag; Chanan, Moch (Journal of Forest Science Avicennia, 2019)
Edelweiss for the tenggerese is the sacred plant, when the Edelweiss became extinct then it will affect the cultural customs of tenggerese. To cope with the extinction of the Edelweiss TNBTS party empower indigenous peoples by creating a tourist village of Edelweiss to maintain continuity, Edelweiss and used to meet the needs of the indigenous. Edelweiss as indigenous because needs as a form of devotion to the deities match the trust community Perched on the Wonokitri. This research aims at 1) to determine the strategy of the development of Village Tourism Edelweiss, 2) to find out the participation of the community. The method used a qualitative descriptive analysis is used to find out the participation of the community. The SWOT analysis is used to determine the development strategy of the tourist village of Edelweiss and continued with the analysis of the SWOT matrix. Research results indicate that the development is done Developing Tourism towards Community Based Tourism; utilization and optimization of tourist attractions with the tourist destination with the elements of education, conservation, culture and economic activity of the community; build and improve the means and infrastructure maintenance tourism is necessary; and increase the promotion and development of better program to attract tourists; as well as conducting training to foster community empowerment and raising public awareness about the management of the tourist village. Participation form community Â± 20 persons became a member of the Edelweiss group of farmers manage tourism village of Edelweiss and society did not enter the participating farmers group planted in front of the Edelweiss home and along the way as well as just promoting tourism.